Menstrual Blood Human Papillomavirus DNA and TAP1 Gene Polymorphisms as Potential Biomarkers for Screening and Monitoring of Cervical Squamous Intraepithelial Lesion - Wong, Sze Chuen Cesar; Au, Thomas Chi Chuen; Chan, Sammy Chung Sum; Ng, Lawrence Po Wah; Tsang, Hin Fung (The Journal of infectious diseases, 2018)
Human papillomavirus (HPV) is a known causative factor in the etiology of cervical cancer. HPV DNA genotyping was performed in menstrual blood (MB) collected in napkins from patients with cervical intraepithelial neoplasia (CIN), HPV infection and sexually active apparently normal subjects. In the same patient cohort, MB TAP1 I333V and TAP1 D637G gene polymorphisms were examined. The sensitivity, specificity, and positive and negative predictive values of HPV DNA in the detection of CIN or HPV infection were 83% (223 of 268), 98% (131 of 134), 99% (223 of 226), and 74% (131 of 176), respectively. Moreover, HPV DNA was found in 24% (28/118) patients who had loop electrosurgical excision procedure treatment and 0% (0/76) HPV infected or CIN1 patient with proven recovery. On the other hand, the risk of developing high-grade CIN was significantly reduced for AG and GG genotypes compared with AA genotype and for carriers with a G allele compared with those with an A allele for both polymorphisms. MB HPV DNA is a potential noninvasive marker for screening and monitoring of squamous intraepithelial lesion. Together with TAP1 I333V and TAP1 D637G gene polymorphisms, the combined test may be useful for stratifying high-risk patients for better follow-up strategies.